1975
DOI: 10.1128/jb.121.3.1203-1207.1975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tsl mutations in decreasing radiation sensitivity of a recA- strain of Escherichia coli K-12

Abstract: It has been shown previously that the radiation sensitivity of lexA- strains of Escherichia coli K-12 can be suppressed by thermosensitive mutations (designated tsl) that are closely linked to the lexA locus and are thought to be intragenic suppressors of lexA mutations (Mount et al., 1973). When a recA mutation is crossed into a suppressed tsl- strain, the extreme radiation sensitivity usually conferred by a recA mutation is decreased, but there is no detectable change in genetic recombination deficiency. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…For tif mutagenesis, exponential-phase cultures growing at 30°C in EMM at a concentration of 1 x i05 to 2 x 10" bacteria per ml were centrifuged, suspended in 10 2 M MgSO4, and plated at 30 and 42°C onto histidine-limiting (0.8 ,ug/ ml) minimal medium plates supplemented with adenine (100 ,g/ml). For UV mutagenesis, exponential cultures were centrifuged, suspended in M63 buffer, UV irradiated or not treated, and plated in the dark at 30 and 42°C onto semienriched minimal medium plates. Prototrophic His' revertants were titrated by spreading 0.1-ml portions of undiluted cultures and incubating for 72 h. During this time, the growthlimiting amount of histidine was depleted, and only the His' revertants were able to form colonies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For tif mutagenesis, exponential-phase cultures growing at 30°C in EMM at a concentration of 1 x i05 to 2 x 10" bacteria per ml were centrifuged, suspended in 10 2 M MgSO4, and plated at 30 and 42°C onto histidine-limiting (0.8 ,ug/ ml) minimal medium plates supplemented with adenine (100 ,g/ml). For UV mutagenesis, exponential cultures were centrifuged, suspended in M63 buffer, UV irradiated or not treated, and plated in the dark at 30 and 42°C onto semienriched minimal medium plates. Prototrophic His' revertants were titrated by spreading 0.1-ml portions of undiluted cultures and incubating for 72 h. During this time, the growthlimiting amount of histidine was depleted, and only the His' revertants were able to form colonies.…”
Section: Methodsmentioning
confidence: 99%
“…The very interesting tsl mutations, which have been isolated from UV-resistant pseudorevertants of lexA mutants and are probably located in the lexA gene (29), cause thermal induction of fiamentation and of recA protein synthesis without a concomitant induction of A prophage (17,28). This partial induction, unlike all other known means of inducing the SOS response, does not depend on normal recA function, for it takes place in a tsl-l recAl strain at 42°C (17,30).…”
mentioning
confidence: 99%
“…In combination with the unusual missense recAl mutation, which apparently retains some repair activity of the recA+ protein, tsl causes the accumulation of an altered, recAl-modified protein X (10,18). This accumulation in tsl recAl versus tsl+ recAI has been correlated with (i) an increased UV resistance (8), (ii) an enhanced capacity to perform postreplication repair (8), and (iii) an errorfree repair process acting on UV-X (19); all three phenomena were found to be uvrA' dependent (8,19). Besides again implicating the uvr excision function in postreplication repair, these data further suggest that the tsl-stimulated uvr'-dependent repair in the recAl background and the tif-stimulated uvr'-dependent repair reported in this paper may be identical.…”
Section: 2mentioning
confidence: 99%
“…To the contrary, in an earlier study, suggested that the development of radio-resistance was a result of selection that favored mutations leading to the increased radioresistance and not a result of increased capacity to repair microbial DNA. However, Mount et al (1975) demonstrated that some mutations increase radio-resistance of recA strain of E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…This E. coli contains mutations of the recA and gyrA genes that are necessary for DNA repair and replication. Therefore, recA and gyrA mutants have impaired ability to repair and recombine their DNA strands making the mutants sensitive to ionizing radiation, ultra violet (UV), and chemicals (Bridges 1971, Mount et al 1975, Sedgwick and Bridges 1972, Cox 2007, Orser et al 1995, Kornberg and Baker 2005. Therefore, studying microbial inactivation kinetics of this DNA-repair deficient E. coli DH5α in a staple food such as fresh ground beef will enhance understanding of microbial radio-resistance to e-beam and may indicate some other, genetic or non-genetic factors involved in radio-resistance.…”
Section: Radiomentioning
confidence: 99%